Balochistan : Architecture, Craft, and Religious Symbolism - Keiany, Mohsen (Karachi Oxford University Press, 2015)
This research work explores the living tradition of Baluchistan and provides a deeper understanding of its religo-cultural aspects. The research first focuses on the social environment of Baluchistan, in order to understand the input of local culture and tribo-religious influences of local architecture. The Baluchi lifestyle is analysed on a broad plane, taking into account native architecture including mosques and symbolic minarets as key factors, together with their design, characteristics, social contextualisation and methods of production.
Include Figures, Tables, Bibliography and Glossary and Index.
Architecture, Craft, and Religious Symbolism.
Keywords: Teachers--Training of -- Inclusive education -- South Africa -- Criminology